Agritourism in academic research: Literature review and cluster analysis - Roman, Michał; Kawęcki, Norbert (Turyzm/Tourism, 2024)
The aim of the article is to review the current literature in the field of agritourism. The data for the analysis was collected from the Web of Science database from 1990–2022: a total of 1,834 bibliometric publication records. The article presents both quantitative and qualitative analysis. The results indicated five main research areas: (a) the impact of the attitudes of the community on the perception and management of ecotourism and agritourism; (b) the impact of models of the perception of the quality of services in agritourism on customer satisfaction; (c) the quality of services and tourist culinary experiences that motivate the choice of agritourism destinations; (d) the typology of agritourism farms and their differentiation in the development of rural tourism; (e) the impact of state policy on the management of rural tourism and agritourism. The limitations of the conducted research, which mainly concern the methodological part, should also be borne in mind: including the selected publication database, and search criteria such as publication year or language.